2016
DOI: 10.31254/jmr.2016.2305
|View full text |Cite
|
Sign up to set email alerts
|

Medication Package inserts, concept among doctors pharmacists and laypersons- A beneficial guidance or a source of confusion

Abstract: Increasing emphasis on the importance of the package insert we tend to designed a questionnaire to work out the perspective of physicians, pharmacists and laypersons of Karachi towards package inserts (PI) for medication data. The sample size of our study was 270 that embody ninety physicians, ninety pharmacists and ninety laypersons. The study explore the results of the survey that the majority of respondents (93.7%) are aware about the packaging Insert (PI) or showed the positive response about awareness to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…All these emerging issues aggravate the need of providing a detailed PI in every drug formulations. Several studies have demonstrated that a good PI with accurate reliable and approved information can provide a desirable better health outcome (Khafeel et al) [4].…”
Section: Introductionmentioning
confidence: 99%
“…All these emerging issues aggravate the need of providing a detailed PI in every drug formulations. Several studies have demonstrated that a good PI with accurate reliable and approved information can provide a desirable better health outcome (Khafeel et al) [4].…”
Section: Introductionmentioning
confidence: 99%
“…3 A survey based study done by Kafeel et al analyzed that 75.6% responders believed that reading package inserts affect health outcomes. 4 It is written in a non-promotional, nonmisleading and easy to understand language. In India, the standards of package insert are formalized by the 'drugs and cosmetics act (1940) and rules (1945).…”
Section: Introductionmentioning
confidence: 99%